2013
DOI: 10.4163/jnh.2013.46.5.418
|View full text |Cite
|
Sign up to set email alerts
|

Association between picky eating behaviors and growth in preschool children

Abstract: This study was conducted in order to investigate the association between picky eating behaviors of preschool children and growth outcomes. In this study, picky eating behaviors were defined as containing four constructs of 'eating a small amount (ES),' 'neophoic behavior (NB),' 'refusal of specific food groups (RF),' and 'preference for specific foodpreparation methods (PP).' A 7-point scale was used for the multi-item questionnaire, which consisted of 21 items (three items for ES, two items for NB, nine items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…“Eating small amounts” refers to consuming insufficient food, and “limited variety” includes “neophobic behavior”, which refers to avoiding new foods and a “refusal of specific food groups” as well as a “preference for a specific preparation method”, which refers to children’s likes and dislikes of specific foods and certain recipes for each food [19,23]. While children show more than one construct behavior simultaneously and the classification of children overlapped, this approach could find a specific association between children’s eating behaviors and diet and growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…“Eating small amounts” refers to consuming insufficient food, and “limited variety” includes “neophobic behavior”, which refers to avoiding new foods and a “refusal of specific food groups” as well as a “preference for a specific preparation method”, which refers to children’s likes and dislikes of specific foods and certain recipes for each food [19,23]. While children show more than one construct behavior simultaneously and the classification of children overlapped, this approach could find a specific association between children’s eating behaviors and diet and growth.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies have tried to present a clear definition of picky eating, and have characterized children’s picky eating behaviors with two attributes based on previously-reported aspects of picky eating behaviors: eating small amounts of food, and eating a limited variety of foods [ 19 , 23 ]. In the studies, “limited variety” consisted of three sub-constructs of “unwillingness to try new food”, “rejection of specific food groups” (i.e., fruits, vegetables, meats, and fish), and “preference for specific food preparation methods”.…”
Section: Introductionmentioning
confidence: 99%
“…Most countries, including Sweden [9], specify RDAs of carbohydrate, protein, and fat for young children in their nutrition recommendation. In Korea, carbohydrates are staple foods, so management of fat and protein intake for young children is a major concern [4,6,7,20,21]. Especially, menus related to protein and fat are interrelated, so clustering is possible.…”
Section: Prediction Of Growth In a Monthmentioning
confidence: 99%
“…Shim et al [4] conducted the study to investigate the association between picky eating behaviors of preschool children and growth outcomes. ey de ned picky eating behaviors as the four constructs: eating a small amount (ES), neophobic behavior (NB), refusal of speci c food groups (RF), and preference for speci c food preparation methods (PP).…”
Section: Introductionmentioning
confidence: 99%
“…Talley [ 13 ] and Tack [ 14 ] showed that early satiety is associated with a lower BMI. Picky eating is a possible risk factor for thinness or underweight status [ 15 16 ]. Children with eating problems may gain less weight, and children with picky eating behaviors may be at increased risk of being underweight.…”
Section: Introductionmentioning
confidence: 99%